Formação docente em artes visuais na Universidade Estadual de Londrina : um estudo dos currículos sob a perspectiva dos professores egressos - Silva, Renan dos Santos (2019)
This communication comes from a research for a PhD. The investigation looked for learning the constructive lineation of the resumes of the Visual Arts Course from the State University of Londrina – UEL, from which an exploratory study was chosen and, from another part, convergent, the perceptions that the graduated teachers of the Course make of their formation resume and, for such, we choose for the case study. So, it was concluded that there is a need for internal articulation on the resume of the Visual Arts Course, as well as this dialogue between the resume and the school culture